The Factors Affecting The Speed of PPT Innovation Adoption in The Rice Field SL-PTT Program - Daryadi, Yaya; Azhari, Ahmad Shofiyuddin; Firdaus, Muhammad Azzam; Faqih, Achmad (Green Publisher Indonesia, 2023)
This study aims to determine: (1) the effect of the nature of innovation, the nature of potential users, innovation decision-making, communication channels and PPL qualifications simultaneously on the speed of adoption of PTT innovations in the lowland rice SL-PTT program, and (2) the effect of the nature of innovation, the nature of potential users, innovation decision making, communication channels and PPL qualifications partially on the speed of adoption of PTT innovations in the lowland rice SL-PTT program. The research design used in this study is a quantitative research with a quantitative descriptive survey technique. The sampling method used was the census technique, meaning that 20 members of the farmer group working on lowland rice farming were taken as samples. To determine the effect of the independent variables, namely the influencing factors (nature of innovation, nature of prospective users, decision-making, communication/media channels and PPL qualifications) on the speed of adoption of the SLPTT program of lowland rice cultivation, a multiple linear regression model test was used. The results showed that: (1) The nature of innovation, the nature of potential users, innovation decision-making, communication channels and PPL qualifications simultaneously had a significant effect on the speed of adoption of PTT innovations in the lowland rice SL-PTT program, and (2) The nature of innovation, the nature of candidates users, innovation decision making, communication channels and PPL qualifications partially have a significant positive effect on the speed of adoption of PTT innovations in the lowland rice SL-PTT program.